Advancements in phase change materials for nearly zero energy building design: a review - Suqi, Wang; Ahmad Zawawi, Emma Marinie; Qi, Jie Kwong; Yihan, Wu; Congxiang, Tian (UiTM Press, 2025)
Nearly Zero Energy Building (NZEB) leverage passive architectural design and active energy-saving technologies to create comfortable indoor environments while minimising energy use. This study aims to explore the utilisation of Phase Change Materials (PCM) to enhance the thermal inertia of building envelopes, reduce indoor temperature fluctuations, and decrease the capacity requirements of heating and cooling systems. The methodology involves a comprehensive review of the categorisation and properties of PCM, examining their integration with solar, air, and other renewable energy sources. The findings indicate that phase change materials applications in walls, windows, roofs, and floors can significantly enhance thermal inertia, reduce indoor temperature fluctuations, and improve energy efficiency. Additionally, incorporating nanoparticles such as Al₂O₃, TiO₂, and ZnO into PCM has been shown to enhance thermal conductivity, further optimising heat storage performance. The use of PCM presents an efficient and sustainable strategy for improving the energy performance of NZEBs. This study provides a valuable reference for the study and design of nearly zero energy buildings, emphasising sustainability and energy efficiency.